The Migrant Subject in the Novels of the Colombian Writer Óscar Godoy Barbosa (2018)
This paper studies the novels of the Colombian writer Óscar Godoy Barbosa from the perspective of the city as chaotic space causing conflict in the subject related to contemporary urban life. Duelo de miradas [Duel of Glances] , El arreglo [The Fix] and Once días de noviembre[Eleven Days of November] are novels whose plot is developed most of all in Bogotá, Colombian capital; as can be identified by differ-ent literal references. The protagonists of the three novels experience migratory processes common to Colombia and Latin America after 1950. Overpopulation and the proliferation of cultures and customs are accentuated by the rush for progress. This tends to quickly demolish spaces which are loaded with meaning for the characters, affecting the configuration of their identity and generating a condition of abandonment and loss of bearings. Characters frequently drift through the city with no fixed purpose, overcome by their own conflict.